Implementasi Politik Bisnis dalam Mendukung Program Keberlanjutan: Studi Kasus Prudential Life Assurance Indonesia - Wulandari, Ai Malita; Nur’aini, Intan; Nugraha, Nayla Rubayyina; Nurasiah, Sofa Parihah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the implementation of business politics in supporting sustainability programs at Prudential Life Assurance Indonesia. The research employed a qualitative approach using a case study method through document analysis of sustainability reports, annual reports, Financial Services Authority (OJK) regulations, the company’s official website, scholarly journals, and other supporting sources. Data were analyzed using thematic analysis by examining the dimensions of external business politics, internal business politics, and the implementation of sustainability programs. The findings indicate that external business politics is reflected in the company’s compliance with OJK regulations, active participation in industry associations, and transparent sustainability reporting. Meanwhile, internal business politics is demonstrated through management commitment and coordination among business units in implementing the company’s three sustainability strategy pillars. The synergy between these two dimensions supports the consistent implementation of Environmental, Social, and Governance (ESG) principles, resulting in various sustainability initiatives that have received recognition through the ESG Award 2023 and ESG Recognized Commitment 2024. This study concludes that Business Politics Theory is relevant in explaining the successful implementation of corporate sustainability through the management of relationships with regulators, stakeholders, and the strengthening of internal corporate governance.